Renaissance thinkers: Erasmus, Bacon, More, Montaigne - James McConica et al. (Oxford Univ, 1993)
The book contains studies of four of most important philosophical writers of the European Renaissance. All were learned in the literacy classics of ancient Greece and Rome, and they all assumed that the insights of pagan antiquity retained their validity in the Christian era. Erasmus and More believed that the highest human good lay in a union of classical wisdom and Christian teaching, Montaign displayed a more sceptical temper, while Bacon sketched out of scientific programme which was intended to supersede the authority of classical antiquity and literacy humanism altogether